Market discipline and deposit insurance in Russia - Anatoly Peresetsky (Bank of Finland, Institute for Economies in Transition (BOFIT), 2008)
The paper presents a study of Russian banks' interest rates on household deposits during the formation period of the deposit insurance system. It is shown that market discipline weakened after deposit insurance was effectively in place.
URN:NBN:fi:bof-201408072109
Keywords: G21; G28; P37; 330; deposit insurance; market discipline; deposit interest rates